A New Method for Microplastics Identification in Copepods - Thery, Jérémy; Bialais, Capucine; Kazour, Maria; Moreau, Myriam; Dufour, Dylan; Benali, Samira; Amara, Rachid; Monchy, Sébastien; Raquez, Jean-Marie; Souissi, Sami (Frontiers in Environmental Chemistry, 2022)
This study investigates several methods to identify microplastics (MPs) of small size ranges (<10µm) in the copepod Eurytemora affinis collected in the Seine estuary (France) and identified using epifluorescence microscopy and Raman microspectroscopy. In order to calibrate the methodology, copepods obtained from cultures were used. Firstly, we labelled three types of MPs (i.e., Polystyrene, Polyethylene and Polylactic acid) with Nile Red and confirmed their ingestion by E. affinis with epifluorescence microscopy. Considering the convenient detection of Nile Red labelled MPs using epifluorescence observation, we tried to pair this method with Raman microspectroscopy. For this, we developed an enzymatic digestion method consisting of copepods digestion using Proteinase K followed by sonication in order to fragment their cuticle. The lysate was then vacuum filtered on black polycarbonate membrane filters that were the most appropriate for epifluorescence microscopy. Potential MPs were dyed with Nile Red directly on the filter, which allowed a relatively rapid visual detection. However, results showed that black polycarbonate membrane filters induced a significant background fluorescence during Raman identification of MPs and hence particles smaller than 10 µm could not be characterized. In this case, we were not able to link staining method with micro-Raman for the size range of MPs targeted in this study. Thus, aluminum oxide filters were tested, and staining method was replaced by a classical observation with stereomicroscopic magnifier to delimit areas of observation for Raman microscopic identification. Aluminum oxide filters induced less fluorescence, allowing the detection of MPs (as small as 1µm diameter) on copepods from laboratory cultures exposed with MPs. We applied this method on copepods collected in the natural environment. Within a pool of 20 copepods of 3 replicates, we identified 17 MPs (average of 0.28 MPs /copepod) composed of 8 different polymer types and 6 colors. These MPs corresponded to 59% of fibres with 14.1 ± 9.4 µm diameter and 391.6 ± 600.4 µm length along with 41% of fragments with an average diameter of 13.2µm ± 9.5µm. This study reports a novel approach to detect the presence of small particles of MPs ingested by copepods in the natural environment.